Rising to the occasion: outlining Ethnobiologists’ response to the coronavirus (COVID-19) pandemic - Franco, F. Merlin; Bussmann, Rainer W (Ethnobotany Research and Applications, 2020)
The COVID-19 pandemic has emerged as the greatest threat to humankind so far in the 21st Century. As of 27th May 2020, there were 5,717,726 reported cases, and 352,983 fatalities (WHO 2020). The pandemic is not just a health crisis anymore, because lockdowns and other restrictions have greatly affected economic activities, which in turn affects cash flows in local and regional scales. Closure of businesses lead to widespread rise in unemployment, further leading to socio-economic problems, and reduction of public expenditure available for healthcare (McKee & Stuckler 2020). The health and economic impacts are predicted to be even much more serious in indigenous communities who live in remote areas and suffer institutional apathy (Ferrante & Fearnside 2020). Such a situation underlines the need for Ethnobotanists to rise to the situation and complement the ongoing efforts from our communities and local governments in combating COVID-19 and its impacts.